Dinamika Stres Psikososial dalam Lingkaran Pertemanan Pada Pengguna Pinjaman Online di Kalangan Remaja - Astarini, Dilla; Silianti, Silianti; Royani, Winda (Yayasan Sembilan Pemuda Indonesia, 2025)
This study explores psychosocial stress among online loan users, focusing on peer group dynamics. Using a qualitative descriptive method with a literature review approach, the study identifies key stress indicators such as social withdrawal, anxiety, and interpersonal tension. The findings suggest that online borrowing behaviors often lead to strained peer relationships and deteriorating mental health. Counseling strategies and financial literacy education are recommended to mitigate these impacts.